Electrochemical Sensors and Biosensors Based on Graphene Functionalized with Metal Oxide Nanostructures for Healthcare Applications. Issue 18 (14th May 2019) - Kumar, Sudesh; Bukkitgar, Shikandar D.; Singh, Supriya; Pratibha,; Singh, Vanshika; Reddy, Kakarla Raghava; Shetti, Nagaraj P.; Venkata Reddy, Ch.; Sadhu, Veera; Naveen, S.
Abstract: Graphene has attracted wide consideration in recent years to the assembly of sensitive sensors and biosensors due to its unique and remarkable physical and electrochemical properties. Moreover, graphene, as an essential two‐dimensional carbon material with remarkably high quartz and electronic superiority, has also received significant research attention. This review presents the different synthesis techniques of graphene; graphene functionalized based electrochemical sensors and biosensors for various health care appellations. Further, were discussed on the basis of enhanced catalytic activity, improved detection limit in conjunction with sensitivity, and selectivity. Synergistic action of graphene and metal oxide nanostructure has contributed towards high activity as a biosensing material. The results with different sensors and biosensors for the detection of significant biomarkers such as protein sensor, electrochemical immune sensor, phytochrome sensor, cholesterol biosensor glucose, hydrogen peroxide, and nicotinamide adenine dinucleotide detection sensor etc., and highlighted the use of graphene and functionalized graphene in different sensing platforms. Finally, the challenges related to less aggregated graphene‐based electrochemical sensors and biosensors as well as future research directions are discussed. Abstract : Electrochemical biosensors exploiting nanomaterials have lately attracted significant consideration in the areas of sensing. When nanostructured metal oxides when dis on nanoparticles of conducting or semiconducting materials such as graphene, they easily contribute towards advantages such as improved biosensor characteristics. Since the discovery in 2004, graphene (GR) has gained remarkable attention due to its varied properties such as thermal conductivity, strong Young's modulus high surface area, optical transparency, and electric conductivity. These further can be incorporated towards health care application.